Wearable thermoelectric generator for harvesting human body heat energy - Kim, Min-Ki; Kim, Myoung-Soo; Lee, Seok; Kim, Chulki; Kim, Yong-Jun (Smart materials and structures, 2014)
This paper presents the realization of a wearable thermoelectric generator (TEG) in fabric for use in clothing. A TEG was fabricated by dispenser printing of Bi0.5Sb1.5Te3 and Bi2Se0.3Te2.7 in a polymer-based fabric. The prototype consisted of 12 thermocouples connected by conductive thread over an area of 6 × 25 mm2. The device generated a power of 224 nW for a temperature difference of 15 K. When the TEG was used on the human body, the measured output power was 224 nW in an ambient temperature of 5 °C. The power of the TEG was affected by the movement of the wearer. A higher voltage was maintained while walking than in a stationary state. In addition, the device did not deform after it was bent and stretched several times. The prospect of using the TEG in clothing applications was confirmed under realistic conditions.